DIGITAL LANGUAGE LABORATORY: A RESUSCITATIVE INNOVATION IN ORAL ENGLISH PEDAGOGY IN TERTIARY INSTITUTIONS IN ENUGU STATE - Mrs. Eze, Edith (Journal of Current Research and Review (JCRR), 2022)
This study was designed to examine the significance of the individual and collective contributions to students’ learning of oral English via the Digital Language Laboratory. Based on this, one research question and one hypothesis were formulated to guide the study. The study is quasi experimental design which involved the use of intact classes. All seventy-seven year one students of the Department of Language Studies, Enugu State College of Education (Technical) ESCET, Enugu and sixty students of the Department of Language Studies, Institute of Ecumenical Education Thinkers Corner, Enugu were used for the study. In assigning the subjects to control and experimental group, the seventy-seven students of ESCET and sixty students of Ecumenical were used respectively. The experimental group was exposed to Digital Laboratory Instructional Resource Mode while the control group was exposed to the Presentation Instructional Mode of teaching. The instrument used for the study was Oral Production Test, the scores obtained from the pre-test were used for item analysis and calculation of reliability indices. Applying Kuder-Richardson formula 20 the reliability indices of 0.98 was found. The mean scores and the standard deviations were computed and were used for answering research question, while the analysis of covariance was adopted to test the hypothesis. It was found that Digital Language Laboratory Mode of teaching oral English was significantly more effective than the Presentation Instructional Mode. The results of the study show that the use of Digital Language Laboratory Instructional Mode enhances instruction on oral English. It was recommended that oral English teachers should adopt the use of Digital Language Laboratory as an instructional mode of teaching phonetics and phonology.